Objective Assessment of Cough: An Early Marker of Response to Biological Therapies in Asthma? - Faruqi, Shoaib; Sykes, Dominic L.; Crooks, Michael G.; Brindle, Kayleigh; Thompson, Joanne; Morice, Alyn H. (Lung, 2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Cough is an important symptom of asthma. The objective assessment of chronic cough has been enhanced by the development of ambulatory cough monitoring systems. Mepolizumab has been demonstrated to reduce exacerbations in eosinophilic asthmatics long-term. We evaluate the utility of objective cough count as an outcome measure in severe eosinophilic asthma treated with mepolizumab. Consecutive, consenting patients initiated on treatment with mepolizumab had a 24-h cough count recorded at baseline; this was repeated at 1, 3 and 6 months. Asthma control questionnaire (ACQ) scores and exacerbation frequency were also recorded. The mean 24-h cough count in 11 subjects (8 females, mean age 53.6 years) was 172.4 at baseline; at 1, 3 and 6 months following initiation of treatment this decreased to 101.4, 92 and 70.8, respectively (p < 0.02). Significant improvements were also observed in mean ACQ score (3–1.6, p < 0.01) and exacerbation frequency (5.5 per year – 1.3, p < 0.01). Objective cough measurement could be used as an early, precise and clinically relevant endpoint in assessing response to asthma therapy.